Magic efficiency of approximation of smooth functions by weighted means of two N-point Padé approximants - Gilewicz, J.; Jedynak, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider the approximation of smooth functions by two weighted N-point Pad´e approximants. We present numerical examples and the inequalities between the Stietjes function and its N-point Padé approximant. Квартиры посуточно - онлайн-бронирование